The Cognitive Economy: An approach to Developing the Faculties of Education Competitive Abilities - Mohamed Mostafa Mohamed Mostafa; Basem Soliman Saleh (European Scientific Journal, ESJ, 2016)
The current study aimes at recognizing the cognitive economy reality at the faculties of education and the effect of its dimensions on developing the competitive abilities of the faculties of education. The two researchers used the perspective method . Two questionnaires were prepared. The first one was applied on a sample of staff members at the faculties of education, which it concluded (117) person in order to; recognize the reality of the cognitive economy at the faculties of education and the effect of its dimensions on developing their competitive abilities. The second questionnaire was applied on the same previous sample in order to; recognize the requirements of the cognitive economy at the faculties of education to increase its competitive abilities. The study came down to several results, most important of which were the agreement of the sample individuals, as whole, that ,the requirements of the cognitive economy at the faculties of education that increase its competitive abilities, were represented in evolving information technology and telecoms, the curriculum, the service and research programs, enabling staff members to participate in the activities of information mobility of human principals among universities, giving students the technological skills concerning the international markets and sharing at the unions of the pioneering international universities in the field of information technology and telecoms. The researcher concluded with setting a suggested proposal that included aims, fundamentals, mechanisms and guarantees to achieve the cognitive economy as an Approach to developing the competitive abilities of the faculties of education.